The Relationship between Psychological Lifestyle and Spiritual Intelligence among Women - Zahra Shirzadi; Reza Khakpour; Anahita khodabakhshi-koolaee (Zanjan University of Medical Sciences and Health Services, 2021)
Background: According to Adler, lifestyle reflects the individual's unique, unconscious, and repetitive way of responding to or avoiding main living routines: friendship, love, work, spirituality, family, and self-acceptance. Lifestyle is related to spirituality, as well as the life solutions chosen by a person. Objectives: The present study aimed to examine the relationship between psychological lifestyle and spiritual intelligence in women. Methods: In this descriptive-correlational study, all the women referred to counseling centers and health clinics in districts five and six of Tehran in 2020. The participants were 400 women who met our inclusion criteria and volunteered to participate in the study, chosen by the convenience sampling method. For calculating the sample size, we used the Cochran formula. The data were collected using the Self-Report Measure of Spiritual Intelligence (King & DeCicco, 2009) and Adlerian-Based Lifestyle Assessment (Curlette, Wheeler, & Kern, 1993) tools. The collected data were analyzed using the Pearson correlation test by SPSS 16. Results: The results indicated that 32% of the women were 26 to 30 years old, 38.75% of them had a diploma, and 35.2% had two children. The findings showed a significant and positive relationship between lifestyle and spiritual intelligence (P<0.01), indicating that the higher a person's lifestyle score was, the higher his/her level of spiritual intelligence would be. Conclusion: Studies have shown that lifestyle, a sense of belonging, going along, taking charge, wanting recognition, and being cautious, plays a decisive role throughout a person's social, professional, marital, and physical lives, as well as his/her spiritual intelligence. Our findings can be used for educating, guiding, and counseling women to appropriately modify their life styles.